The Finance and Growth Nexus Re-Examined : Do All Countries Benefit Equally? - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 2013)
A large theoretical and empirical literature has focused on the impact of financial deepening on economic growth throughout the world. This paper contributes to the literature by investigating whether this impact differs across regions, income levels, and types of economy. Using a rich dataset for 150 countries for the period 1975-2005, dynamic panel estimation results suggest that the beneficial effect of financial deepening on economic growth in fact displays measurable heterogeneity; it is generally smaller in oil exporting countries; in certain regions, such as the Middle East and North Africa (MENA); and in lower-income countries. Further analysis suggests that these differences might be driven by regulatory/supervisory characteristics and related to differences in the ability to provide widespread access to financial services.